Surgical treatment of type I neuritis in a teenage boy with borderline tuberculoid leprosy - Sette, Christiane Salgado; Wachholz, Patrick Alexander [UNESP]; Masuda, Paula Yoshiko; Fortes da Costa Figueira, Renata Borges; Cury Filho, Milton; Soares, Cleverson Teixeira; Barreto, Jaison Antonio (Soc Brasileira Medicina Tropical, 2015)
Exacerbation of the immune response against Mycobacterium leprae can lead to neuritis, which is commonly treated via immunosuppression with corticosteroids. Early neurolysis may be performed concurrently, especially in young patients with a risk of functional sequelae. We report the case of a young patient experienced intense pain in the left elbow one year after the treatment of tuberculoid-tuberculoid leprosy. The pain was associated with paresthesias in the ulnar edge and left ulnar claw. After evaluation, the diagnosis was changed to borderline tuberculoid leprosy accompanied with neuritis of the left ulnar nerve. Early neurolysis resulted in rapid reduction of the pain and recovery of motor function.
Keywords: Borderline leprosy; Neuritis; Leprosy therapy; Minor surgical procedures; Leprosy surgery